Simplified and Refined Analyses for Seismic Investigation of Historical Masonry Clusters: Comparison of Results and Influence of the Structural Units Position - Chiumiento, Giovanni; Formisano, Antonio (Frontiers in Built Environment, 2019)
The goal of this work is the seismic vulnerability assessment of building aggregates within the historical centre of Arsita (Teramo, Italy), damaged by the 2009 L’Aquila earthquake, by comparing two different analysis procedures applied to a construction compound case study. First, the seismic vulnerability of structural units of the building compound, has been appraised by using a vulnerability evaluation quick form appropriately conceived for masonry aggregates. In particular, heading and intermediate structural units, having different geometrical configuration and seismic behaviour, have been inspected by using the before mentioned form, which allowed to calculate for them a synthetic vulnerability index. Starting from these indexes, the probable damages suffered by the examined structural units under different grade earthquakes have been estimated. Later on, both the single structural units and the whole construction compound have been modelled by using the macro-element refined method foreseen by the 3Muri non-linear analysis software. Static non-linear analyses performed on the above-mentioned structures have provided the related pushover curves, used to estimate, through the N2 method, the damages suffered under seismic actions expected in that site. Therefore, damages of single structural units have been compared to those experienced by the same structures within the building aggregate. Finally, the results deriving from the two analysis methodologies considered have been compared to each other, allowing to confirm the effectiveness of the simplest technique to predict the seismic damage and vulnerability of investigated structures.